Ukuran Perusahaan dan Implikasinya Terhadap Risiko Bisnis Perusahaan Penyedia Jasa Logistik - Budi Prasetiyo; Nofrisel Nofrisel; Edhie Budi Setiawan (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this research is to determine the role of company size and growth to business risk of logistics companies registered in Indonesia Stock Exchange (IDX) period 2013 - 2017. The main problem of the study was the increasing business risk of logistics companies. This research used quantitative method, descriptive and inferential statistics with path analysis. There were 18 companies with five-year observation period taken with a purposive sampling technique that resulted to 90 samples. The result shows that the size of the company could not increase the risk of logistics companies’ business registered in IDX, however, the size could increase company’s growth. The size of the company has implication to the increased risk of logistics companies registered in the IDX.